Differential Rearrangement of Excitatory Inputs to the Medial Prefrontal Cortex in Chronic Pain Models - Jefferson, Taylor; Kelly, Crystle J.; Martina, Marco (Frontiers in Neural Circuits, 2021)
Chronic pain patients suffer a disrupted quality of life not only from the experience of pain itself, but also from comorbid symptoms such as depression, anxiety, cognitive impairment, and sleep disturbances. The heterogeneity of these symptoms support the idea of a major involvement of the cerebral cortex in the chronic pain condition. Accordingly, abundant evidence shows that in chronic pain the activity of the medial prefrontal cortex (mPFC), a brain region that is critical for executive function and working memory, is severely impaired. Excitability of the mPFC depends on the integrated effects of intrinsic excitability and excitatory and inhibitory inputs. The main extracortical sources of excitatory input to the mPFC originate in the thalamus, hippocampus, and amygdala, which allow the mPFC to integrate multiple information streams necessary for cognitive control of pain including sensory information, context, and emotional salience. Recent techniques, such as optogenetic methods of circuit dissection, have made it possible to tease apart the contributions of individual circuit components. Here we review the synaptic properties of these main glutamatergic inputs to the rodent mPFC, how each is altered in animal models of chronic pain, and how these alterations contribute to pain-associated mPFC deactivation. By understanding the contributions of these individual circuit components, we strive to understand the broad spectrum of chronic pain and comorbid pathologies, how they are generated, and how they might be alleviated.